Stress in parents of children with developmental disabilities - Andrijana Bakoč; Olivera Kalajdžić; Ranka Perućica; Ivana Zečević (Биомедицинска истраживања, 2024)
Introduction: The birth of a child with developmental disabilities changes the life of a family, placing before it additional obligations, greater responsibility and facing numerous challenges that can lead to an increase in parental stress. The aim of this research is to examine the level of stress in parents of children with developmental disabilities and determine the difference in stress intensity in relation to individual characteristics of parents (sex, age, educational and work status) and children (type of disability). Method: The sample consisted of 122 respondents, active members of the association of parents of children with developmental disabilities from Eastern Herzegovina and the Sarajevo-Romania region. In the sample, a higher percentage was female respondents (78.72%), while the average age of the respondents was 46.97 years (SD ꞊ 12.04). For the purpose of data collection, a sociodemographic guide and the Stress Symptoms Scale - 16 were used. Results: The subjects of our sample tended to experience a relatively low level of stress (Mdn = 26.5). There were no statistically significant differences in the stress intensity of parents of children with develop mental disabilities in relation to sex, age, work, and education status of the respondents. On the other hand, the statistically significant difference was found in the level of stress manifestation in relation to the type of child’s disability (p = 0.01), whereby parents of children with multiple disabilities experienced the greatest stress, and parents of children with chronic diseases and physical disabilities experienced the least stress. Conclusion: The results indicate the importance of studying this issue in future research in order to empower the families of children with developmental disabilities and reduce parental stress.
Keywords: parents; stress; children with developmental disabilities